Immobilization mechanism of Se oxyanions in geopolymer: Effects of alkaline activators and calcined hydrotalcite additive - Tian, Quanzhi; Guo, Binglin; Sasaki, Keiko (Journal of hazardous materials, 2020)
[Display omitted] •The immobilization of selenite and selenate in geopolymer was explored.•Two kinds of activators were used for geopolymer synthesis.•The effect of calcined hydrotalcite on the Se leaching was discussed.•Electrostatic interaction is the main association mode of selenium in geopolymer.•Compactness of geopolymer plays a critical role in the immobilization of selenium. Geopolymers have been widely adopted to stabilize the cationic pollutants. However, few studies have focused on the immobilization of anionic species. In this study, the immobilization of SeO32– and SeO42– was explored for the first time using geopolymer activated by different alkaline solutions (NaOH and Na2SiO3) with and without calcined hydrotalcite (CHT), characterized by TCLP, XRD, FTIR, TG, NMR, XAFS, and N2 adsorption-desorption isotherm. Na2SiO3-activated geopolymers without CHT additive showed lower leaching percentages of SeO32– and SeO42– (approximately 10 % and 18 %) than NaOH-activated geopolymers (approximately 58 % and 74 %). It has been proven that electrostatic interaction is the main association mode of SeO32– and SeO42– in both NaOH- and Na2SiO3-activated geopolymers. Hence, compactness plays a vital role in the Se leaching from geopolymer. The addition of CHT reduced the compactnesses of both NaOH- and Na2SiO3-geopolymers. Due to the formation of hydrotalcite, the CHT additive contributed to immobilize SeO32– and SeO42– in NaOH-activated geopolymers. However, this phenomenon was not observed in Na2SiO3-activated geopolymers. Thus, the leaching amount of Se greatly increased from Na2SiO3-activated geopolymers with CHT additive. This study provides new insights on the application of geopolymer to immobilize anionic pollutants.